Pendampingan Pembuatan Konten Digital bagi Para Pelaku UMKM untuk Meningkatkan Minat Konsumen - Fauzan, Luthfi Rafif; Adnan, Iis Zilfah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
This research is motivated by the lack of understanding of technology among MSMEs in creating content that can attract consumers in Garut Regency. The purpose of this community service is to help and educate MSME actors in creating good content on social media so that it can attract consumers. The method used in this community service uses a direct mentoring method for MSMEs with several stages including observation, preparation, implementation and evaluation. The results of this service show success where MSME actors are very interactive in this activity to solve their problems and concerns in the content creation process. It is hoped that MSME actors can apply the understanding they gain in this content creation mentoring activity.